2021
DOI: 10.1186/s12905-021-01483-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolated fallopian tube torsion with paraovarian cysts: a case report and literature review

Abstract: Background Isolated fallopian tube torsion (IFTT) is a rare cause of gynecological acute abdomen, is easily misdiagnosed and often has a delay in diagnosis. IFTT with paraovarian cysts is most frequently reported in studies. Here, we reported a patient diagnosed with IFTT associated with a paraovarian cyst, and we conducted a literature review for IFTT, aiming to identify valuable information that will be helpful for diagnosis and treatment for fallopian tube torsions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…If clinical suspicion of adnexal torsion is high and ultrasound is normal, magnetic resonance imaging or diagnostic laparoscopy can be considered. 3 In our patient the ultrasound identified a cyst with normal color doppler of both ovaries but, owing to persistent pain, laparoscopy was performed and torsion of fallopian tube secondary to para‐ovarian cyst was identified (Figure 1B ). In summary, para‐ovarian cyst can cause torsion of adnexal structures.…”
Section: Diagnosismentioning
confidence: 74%
“…If clinical suspicion of adnexal torsion is high and ultrasound is normal, magnetic resonance imaging or diagnostic laparoscopy can be considered. 3 In our patient the ultrasound identified a cyst with normal color doppler of both ovaries but, owing to persistent pain, laparoscopy was performed and torsion of fallopian tube secondary to para‐ovarian cyst was identified (Figure 1B ). In summary, para‐ovarian cyst can cause torsion of adnexal structures.…”
Section: Diagnosismentioning
confidence: 74%
“…Some studies have suggested that right fallopian tube torsion is more common than left fallopian tube torsion because the left side is thought to be fixed by the sigmoid mesentery ( 4 , 6 ). However, according to a recent review, most cases of tubal torsion occur on the left side (14/20) ( 3 ), which contradicts the previously held view. Notably, our case also happened to occur on the left side.…”
Section: Discussionmentioning
confidence: 88%
“…Continuous torsion leads to obstruction of arterial blood supply, which in turn leads to tubal ischemic necrosis ( 2 ). Patients with IFTT may present with various types of abdominal pain—acute or subacute, intermittent or persistent, severe or mild—and are often accompanied by vomiting ( 3 ). Diagnosis of IFTT is often delayed due to these nonspecific clinical manifestations, leading to adnexectomy, which can affect fertility.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] A high index of suspicion is required to diagnose this uncommon condition which can be confirmed and managed only after laparotomy. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%